PENGARUH LUAS LAHAN, PRODUKSI, HARGA KAKAO INTERNASIONAL TERHADAP EKSPOR KAKAO INDONESIA - Suci Indah Hakiki; Asnawi Asnawi (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to examine the effect of land area, production, international cocoa prices on Indonesian cocoa exports. The data used is the time series data for the period 1991-2017. This study uses two methods of analysis multiple linear regression analysis, the second is the Auto Regressive Distributed Lagged (ARDL). The test results using multiple linear regression analysis showed that as together of land area, production, international cocoa prices effected on Indonesian cocoa exports. Partially large areas, production and prices of international cocoa each have a positive and significant effect on Indonesian cocoa exports. The test results using ARDL indicated a cointegration positive and not significant long-run and short-term. Production and prices of international cocoa in long run and short term each influenced positively and significantly.